2021
DOI: 10.1002/gps.5496
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between retinal nerve fibre layer thickness and white matter lesions in Alzheimer's disease

Abstract: Objectives Early diagnosis in Alzheimer's disease (AD) is crucial in order to implement new therapeutic strategies. The retina is embryologically related to the brain. Thus, the possible usefulness of optical coherence tomography (OCT) in the early detection of AD is currently being studied. Our aim was to study the relationship between retinal nerve fiber layer (RNFL) thickness and AD. Methods We undertook an observational, analytical, cross‐sectional study with consecutive sampling of 32 patients with AD or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…Studies have shown that thinning of GC-IPL in AD patients is associated with volume reduction of occipital and temporal lobes (Ong et al, 2015;Carazo-Barrios et al, 2021). In contrast with previous work, no correlation was observed between retinal structure and the volume of hippocampus or V1 in AD patients in our study, probably because most of the patients included in this study were mild-to-moderate AD patients, and the sample size was relatively small.…”
Section: Discussioncontrasting
confidence: 98%
“…Studies have shown that thinning of GC-IPL in AD patients is associated with volume reduction of occipital and temporal lobes (Ong et al, 2015;Carazo-Barrios et al, 2021). In contrast with previous work, no correlation was observed between retinal structure and the volume of hippocampus or V1 in AD patients in our study, probably because most of the patients included in this study were mild-to-moderate AD patients, and the sample size was relatively small.…”
Section: Discussioncontrasting
confidence: 98%
“…Both the macular RNFL thickness and hippocampal volume show a significant decrease in the order of normal subjects, MCI patients, and AD patients, and the macular RNFL thickness showed a significant correlation with hippocampal volume. Another similar study performed by Carazo-Barrios et al (2021) revealed that the mean RNFL thickness of left temporal quadrants was significantly correlated with the number of occipital white matter lesions. None of the aforementioned cross-sectional studies could dynamically describe these parameters such that further longitudinal studies are needed.…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 67%
“…Carazo-Barrios et al (12) showed a relationship between macular RNFL thickness and WM hyperintensities in the occipital region. Jorge et al (3) used MRI and PET with [11C]-Pittsburgh Compound B (PiB) tracer and found a correlation between the retinal inner plexiform layer and primary visual cortex (V1), which also showed greater Aβ deposition.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the retina can be considered "a window through the brain" (14). Patients with AD can suffer from visual deterioration early in the disease, involving decreased visual acuity, abnormal pupillary reaction, or color perception impairment (12,15). Accordingly, retinal examination using optical coherence tomography (OCT) has been proposed to investigate changes associated with AD (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation